For b, lets do something almost exactly like a. Lets have the function f where f(x) = {x/2 if x is even and -(x-1)/2 if x is odd}.

C is probably the easiest one of all. f(x) = -x.

]]>a) Prove that the function f(n)={ 2n, if n>0 and -2n+1, if n ≤ 0} is bijective.

b) Prove that Z ≈ Z+ by finding a bijective function g: Z+ -> Z.

c) Let Z- be the set of negative integers. Prove that Z- ≈ Z+ by finding a bijective function f: Z+ -> Z=. prove that your function is bijective.

I know to prove something is bijective you need to show its surjective and injective, however I'm completely lost from there. Any help?

]]>